2019
DOI: 10.1186/s10020-019-0091-4
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture attenuated cerebral ischemic injury and neuroinflammation through α7nAChR-mediated inhibition of NLRP3 inflammasome in stroke rats

Abstract: Background Our previous research confirmed that electroacupuncture (EA) stimulus elicits neuroprotective effects against cerebral ischemic injury through α7 nicotinic acetylcholine receptor (α7nAChR)-mediated inhibition of high-mobility group box 1 release mechanism. This study investigated whether the signal transducer of α7nAChR and inhibition of NLRP3 inflammasome are involved in the neuroprotective effects of EA stimulus. Methods In adult male Sprague-Dawley rats, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 45 publications
1
53
0
Order By: Relevance
“…Hippocampal NF-κB mRNA expression, and serum TNF-α and IL-1β levels were increased in response to ischemia stroke ( 8 ). Cerebral ischemia-reperfusion injury activated the NLRP3 inflammasome proteins in rats, which could be suppressed by electroacupuncture, leading to improvement of neurological deficit scores and infarct sizes in middle cerebral artery occlusion (MCAO) model rats ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hippocampal NF-κB mRNA expression, and serum TNF-α and IL-1β levels were increased in response to ischemia stroke ( 8 ). Cerebral ischemia-reperfusion injury activated the NLRP3 inflammasome proteins in rats, which could be suppressed by electroacupuncture, leading to improvement of neurological deficit scores and infarct sizes in middle cerebral artery occlusion (MCAO) model rats ( 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…Using the PPI-T test, we performed the first pharmacological experiments on the effects of nicotinic receptor (nAChRs) agonists α7 and α4β2 subtypes (respectively PNU-282987 (PNU) and RJR2403) on HBH, in low selective doses equal to their K i and some higher. It is known that nAChRs are involved in hypoxic or ischaemic preconditioning in the brain and other organs, and it was most convincingly demonstrated for the α7 and α4β2nAChRs [ 40 , 41 , 42 , 43 , 44 ]. In our experiments, PNU (but not RJR2403), and more pronouncedly its solvent dimethyl sulfoxide (DMSO, 2–3%), showed a PPI-associated effect on the efficiency of HBH, the direction of which changed to the opposite at the border when PPI = 36–40% [ 20 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…EA at Shuigou (GV26) significantly improved the neurological deficit symptoms in rats with ischemic stroke, which may be involved in upregulating Wnt7a and LEF1 proteins and mRNAs levels and decreasing GSK-3 β and DKK1 proteins and mRNAs levels [ 37 ]. Jiang et al showed a novel anti-inflammatory mechanism induced by EA via α 7nAChR-mediated inhibition of NLRP3 inflammasome in rats after cerebral ischemic injury [ 38 ].…”
Section: The Therapeutic Effect Of Ea For Ischemic Stroke In Expermentioning
confidence: 99%